Evaluation and comparison of Trigonella foenum graecaum (fenugreek) and contraceptive pills antifertility effect on female rats - Hilles, Ayah Rebhi Mohammad (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
Antifertility agents are one of the most common medication used in this modern era. With advances in medical sciences, many natural compounds are also used. One of these herbal plants is Trigonella foenum-graecum (fenugreek). The purpose of this study was to evaluate the anti-fertility effects of fenugreek seeds aqueous (FSA) extract on female rats by determining serum reproductive hormone concentrations and observing their uterus tissue histology, as well as determining the thickness of endometrium uterus, the uterine weight and the implantation rate to compare the effectiveness of fenugreek with marketed combined oral contraceptive pills (COCPs). Twenty four 8-week-old Sprague Dawley rats divided into four groups (A, B, C and D). Animals in Group A (positive control group) were not given any treatment and therefore the rats were pregnant. Groups B (negative control group) were not given any treatment and therefore the rats were not pregnant. Group C (treatment group) were administered orally with 0.05 mg/kg body weight of COCPs. Group C (treatment group) were administered orally with 750 mg/kg body weight of FSA extract for 15 days. Daily vaginal smear cytology was examined. Blood samples were taken by retro orbital technique on day 16 for evaluation of the reproductive hormones assay. Uteruses of the animals were removed for histological study. Administration of 0.05 of COCPs led to decrease the serum FSH concentration to 71.56 ng/ml while 750 mg/kg FSA extract led to decrease it to 25.62 ng/ml which shows that FSA extract effective three times more than COCPs. The endometrium thickness of the uterus in the FSA extract treated group was normal while in the COCPs increased. The uterine weight in the FSA extract treated group was normal while the COCPs treated group was insignificantly high. The uterus tissues in the FSA extract treated group was normal while in the COCPs treated group, there were histopathological changes in the uterine tissues; the glands distribution decrease which a remarkable sign of atrophic endometrium and there were abnormal deciduiod cells (decidual like cells).